Present status of traditional aquaculture and socio-economic condition of fish farmers at Paba upazila in Rajshahi District, Bangladesh - Akter, Sumaiya; Ferdousi, Sultana Shamima; Haque, Md Ayenuddin; Sarker, Md Al Amin (Research in Agriculture Livestock and Fisheries, 2018)
Data were collected from 50 fish farmers through questionnaire interview and Focus Group Discussion (FDG) in Paba upazila, Rajshahi district of Bangladesh during the period of October, 2015 to May, 2016 to evaluate the present status of traditional aquaculture and socio-economic condition of fish farmers. In the study area, average pond size was 0.83 ha (2-7 feet depth) and 80% of the ponds were characterized with loamy soil. Ground water was the main source for 70% of the ponds where about 90% of the fish farmers were engaged in polyculture of carp species. Majority of fish farmers were in the age group of 41-50 years with fish farming experience of 16 years (44%). Activities of DoF were minimum regarding fish farming of the fish farmers. In the present study, 80% of the respondents were related to fish culture as their principal occupation and majority of the fish farmers (50%) have the annual income of BDT 51,000 to 100,000. 30% of the respondents were educated up to secondary level of education. Health and sanitary status are in good condition than before. 94% of fish farmers have improved their socio-economic condition through fish farming. Therefore, proper training on fish farming and advanced technical knowledge are necessary to improve high pond productivity. Res. Agric., Livest. Fish.5(2): 269-277, August 2018